The Effect of Channel Layer Thickness on the Performance of GaN HEMTs for RF Applications - Qian Yu; Sheng Wu; Meng Zhang; Ling Yang; Xu Zou; Hao Lu; Chunzhou Shi; Wenze Gao; Mei Wu; Bin Hou; Gang Qiu; Xiaoning He; et al. (Micromachines)
In this paper, AlGaN/GaN high electron mobility transistors (HEMTs) with different thicknesses of unintentional doping GaN (UID-GaN) channels were compared and discussed. In order to discuss the effect of different thicknesses of the UID-GaN layer on iron-doped tails, both AlGaN/GaN HEMTs share the same 200 nm GaN buffer layer with an Fe-doped concentration of 8 × 1017 cm−3. Due to the different thicknesses of the UID-GaN layer, the concentration of Fe trails reaching the two-dimensional electron gas (2DEG) varies. The breakdown voltage (Vbr) increases with the high concentration of Fe-doped in GaN buffer layer. However, the mobility of the low concentration of the Fe-doped tail is higher than that of the high concentration of the Fe-doped tail. Therefore, the effect of different thicknesses of UID-GaN on the DC and radio frequency (RF) performance of the device needs to be verified. It provides a reference to the epitaxial design for high-performance GaN HEMTs.